Theoretical Study on the Nonlinear Dynamic Response of Propulsion Shafting under Time-Varying Hull Motion - Changyou, Huang; Jianzhong, Hu (Journal of physics. Conference series, 2023)
Due to the effect of external elements such sea waves and sea wind, the ship will unavoidably produce 6 degrees of freedom of movement, with roll motion being the most likely to occur and having the greatest impact. This paper establishes a general dynamic model of the propulsion shafting based on Timoshenko beam theory, the concentrated mass method, and Lagrange’s equation under roll motion and translation motion to study the dynamic behaviour of the propulsion shafting under roll motion and translation motion. FFT, axis trajectory, Poincaré map, and 3D spectrogram were utilized to examine the impact of motion amplitude, frequency, and rotation speed on the propulsion shafting’s dynamic response. The results demonstrated that base motion significantly affects the dynamics of the propulsion shafting, resulting in many components appearing in the system’s response spectrum, and the system changes from quasi-periodic to chaotic motion when base motion amplitude or frequency rises.